Model Manajemen Pendidikan Berbasisi Adab - Gani, Syarif Hidayatullah; Mujahidin, Endin; Sa'diyah, Maemunah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Instilling adab is the most important thing for a teacher to students, because students are a mandate entrusted by Allah to be nurtured, guided, and educated carefully so that later they become useful human beings. The purpose of this research is to find out how the process of managing adab education occurs at MTs Al - Ahsan, Bogor City. The research methodology is a qualitative research method with a descriptive approach. The findings from the research show that the adab education management process is implemented by routinely reading Al-Qur'an Juz 30, praying dhuha in congregation, then continuing with listening to tausiyah and studying the book "Akhlak Lil Banin" and the results of this application are the attitude shown by students can be said to be very satisfying, meaning that the level of success of the activities implemented is very effective in instilling adab in students at school. This can be seen from the enthusiasm of students participating in the activities held by the school. Keywords: Management, Education, Adab